Pelatihan Rescue River Tubing Arung Jeram Water Sport Desa Sintung Kecamatan Pringgarata Lombok Tengah - Akhmad, Noor; Zainuddin, Fadli; Muliyani, Sri Erny; Muhsan, Muhsan; Supriadin, Supriadin (Jurnal Dedikasi Madani, 2024)
River tubing is an activity along a river using a tire or float with a relatively calm to moderate current, suitable for all groups who want to experience the pleasant sensation of waterfalls and the natural surroundings. The Sintung River Tubing white water rafting tourist attraction located in Selakan Hamlet, Sintung Village, Pringgarata District, Central Lombok Regency, West Nusa Tenggara (NTB) offers an exciting experience for visitors who are looking for adventure on the river. It is strategically located in an area rich in nature and rivers that offers an interesting white water rafting experience. Visitors can enjoy white water rafting (river tubing) on the Sintung River. The aim of this service activity is to prevent water accident victims from occurring and how to provide assistance to water accident victims in the rafting tourism awareness group. The method used is counseling on the process of helping water accident victims through the process of delivering material, discussions and field practice. From this service, it was proven that the majority of participants (96%) had gained a good understanding of the concept of "rescue river tubing" after participating in the training and mentoring. The material presented includes an introduction to equipment, basic rescue river tubing techniques, as well as direct practice in using equipment and carrying out rescue river tubing. This activity was carried out to improve the ability to handle accidents in the white water rafting tourist area of Sintung Village, Pringgarata District, Central Lombok Regency.